Primary tooth fluorosis and fluoride intake during the first year of life - Levy SM, Hillis SL, Warren JJ, Broffitt BA, Mahbubul Islam AKM, Wefel JS, Kanellis (Blackwell Synergy, 2002)
Few studies in North America have assessed dental fluorosis of the primary dentition and few, if any, anywhere have assessed the relative importance in fluorosis etiology of fluoride intake during different time periods or from multiple sources.